Mathematics Disability vs. Learning Disability: A 360 Degree Analysis - Nicolson, Roderick Ian; Fawcett, Angela Jocelyn (Frontiers in Psychology, 2021)
We introduce the '360 degree analysis' (360DA) framework and apply it to the overlap between Mathematics Disability (MD) and Reading Disability (RD). The 360DA framework starts by analysing the issue from four perspectives: theoretical, developmental, affective, and pedagogical. Under 360DA these analyses are then integrated to provide insights for theory, and for individual assessment and support, together with directions for future progress. The analyses confirm extensive similarities between arithmetic and reading development in terms of rote learning, executive function and affective trauma, but also major differences in terms of the conceptual needs, the motor coordination needs, and the methods of scaffolding. In terms of theory, commonalities are interpreted naturally in terms of initial general developmental delay followed by domain-independent affective trauma following school failure. Dissociations are interpreted in terms of cerebellar vs hippocampal learning networks, sequential vs spatial processing, and language vs spatial scaffolding, with a further dimension of the need for accurate fixation for reading. The framework has significant theoretical and applied implications